Hydrocarbon Generation History of Tertiary Source Rocks in Phu Khanh Basin, Offshore Vietnam - Nguyen , Trang Thi Thu; Nguyen, Huy Xuan; Nguyen, Van Nguyen; Vo, Thi Hong Quyen (Journal of Earth Energy Engineering, 2020)
The source rock maturity and the hydrocarbon generation history are evaluated in the deepwater Phu Khanh Basin. The average values of heat flow, paleo water depth, and surface-water interface temperatures range from 50.80–61.69 mW/m2, 150-3,500 m, and 2.30-250C, respectively. The Oligocene and Lower–Middle Miocene source rocks are presented. The Oligocene source rock is derived from the lacustrine environment; it is mature to overmature in the Southwest part of the Phu Yen Depression. The main oil phase started in the Early Miocene, and the amount of wet gas occurred only at the bottom part. The Lower-Middle Miocene source rock has been immature in both the Southwest and Northeast part of the Phu Yen Depression. Based on the geochemical analysis, these source rocks were predominantly a mixture of type II and type III kerogens. The total organic carbon and the hydrogen index values range from 1.8-2.5 % and 250-320 mg/g, respectively. The results can help define reservoir locations for future field development planning in the Phu Khanh Basin.